Gender inequality in the labour market of Ukraine: Challenges for the future. (17th October 2022) - Klemparskyi, Mykola M.; Pavlichenko, Helena V.; Prokopiev, Roman Ye.; Mohilevskyi, Leonid V.; Burniagina, Yuliia M.
Abstract : Gender inequality is one of the fundamental manifestations of socio-economic differentiation of the population, leading to different opportunities for self-realisation for women and men in society. This makes it an important topic for analysis even though there may be different views on the matter. The labour market conditions that existed in Ukraine until the end of February 2022 exacerbated the problems of gender inequality in employment. These problems were manifested in unequal opportunities for women and men in public administration, education, employment, income and property. The research uses general and specific scientific methods – dialectical, historical, analysis and synthesis, induction and deduction – to study the legislative frameworks governing gender equality in the European Union (EU) and Ukraine in determining the current state of women's employment in Ukraine and Europe. In this context, the purpose of this article is to identify the features of gender inequality in the labour market of modern Ukraine, as well as to identify its causes and solutions.